A new t-chart using process capability index. Issue 7 (9th August 2017) - Aslam, Muhammad; Mohsin, Muhammad; Jun, Chi-Hyuck
ABSTRACT: Control charts play a vital role to enhance the efficiency of the manufacturing process. In many situations, the quality characteristic of interest to be monitored follows a non-normal distribution. In this article, we propose a new control chart using the process capability index when the quality characteristic follows the exponential distribution. The performance of the proposed chart is evaluated using the Monte Carlo simulation. Tables are presented for various values of specified average run length and sample size. The use of the proposed control chart is discussed with the help of an example.